2022
DOI: 10.1111/anae.15716
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with paediatric airway management during the COVID‐19 pandemic: an international, multicentre, observational study

Abstract: Summary Respiratory adverse events in adults with COVID‐19 undergoing general anaesthesia can be life‐threatening. However, there remains a knowledge gap about respiratory adverse events in children with COVID‐19. We created an international observational registry to collect airway management outcomes in children with COVID‐19 who were having a general anaesthetic. We hypothesised that children with confirmed or suspected COVID‐19 would experience more hypoxaemia and complications than those without. Between 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…To answer this question at the time, members of the International Paediatric Difficult Intubation Collaborative network conducted a prospective multicentre study based on data collected via the paediatric airway complications during COVID‐19 (PAWS‐COVID‐19) collaboration registry. The resulting article [ 7 ], is a good example of an attempt to quickly collect as reliable data as possible to produce clinically useful results in the middle of a chaotic pandemic. The authors should be applauded for their efforts.…”
Section: Covid‐19mentioning
confidence: 99%
See 3 more Smart Citations
“…To answer this question at the time, members of the International Paediatric Difficult Intubation Collaborative network conducted a prospective multicentre study based on data collected via the paediatric airway complications during COVID‐19 (PAWS‐COVID‐19) collaboration registry. The resulting article [ 7 ], is a good example of an attempt to quickly collect as reliable data as possible to produce clinically useful results in the middle of a chaotic pandemic. The authors should be applauded for their efforts.…”
Section: Covid‐19mentioning
confidence: 99%
“…To minimise data collection errors, Peterson et al. [ 7 ] created a robust research collaboration and database structure. Other, ‘fruitful’ national and international success stories in paediatric anaesthesia have been reported over the past decade and continue to thrive (e.g.…”
Section: Other Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased risk is evident even if the patient is asymptomatic at the time of surgery, in both pediatric and adult studies 8,11 . A recent multicenter, international study found children with SARS‐CoV‐2 had a higher incidence of hypoxemia and overall complications during airway management for general anesthesia 15 . These results suggest that SARS‐CoV‐2 disease in children is clinically significant and support current ASA guidelines of delaying surgery if the procedure is not emergent, even if the patient is asymptomatic or their symptoms have resolved.…”
Section: Discussionmentioning
confidence: 99%